Story of the prophet hud: timeless quran stories - KHAN, SANIYASNAIN (GOODWORD BOOKS New Dehli, 2008)
"Story of the Prophet Hud: Timeless Quran Stories" recounts the life and message of Prophet Hud, who was sent to guide the people of 'Aad. The story highlights themes of faith, perseverance, and the consequences of disbelief, emphasizing the importance of worshiping Allah and adhering to His guidance.